Nanocast nitrogen-containing ordered mesoporous carbons from glucosamine for selective CO2 capture. (March 2022) - Maruccia, E.; Lourenço, M.A.O.; Priamushko, T.; Bartoli, M.; Bocchini, S.; Pirri, F.C.; Saracco, G.; Kleitz, F.; Gerbaldi, C.
Abstract: D-glucosamine is investigated as a non-toxic and sustainable carbon/nitrogen (C/N) source for the templated synthesis of nitrogen-containing CMK-8 ordered mesoporous carbons (NOMCs) conceived for selective CO2 uptake. Pyrolysis temperature is varied during nanocasting using the KIT-6 silica hard template to tailor microporosity and nitrogen inclusions. NOMCs exhibit large surface area (600–1000 m 2 g -1 ) and excellent pore ordering. The CO2 /adsorbent interaction energy is estimated by the isosteric enthalpy of adsorption (∼33–40 kJ mol -1 ) and Henry's constants. The role of nitrogen content (∼7–12 at.%) and of each type of N-species on CO2 adsorption is studied by X-ray photoelectron spectroscopy, and CO2 /N2 selectivity is attributed, being pyridinic functionalities the most effective ones. NOMCs are tested at different temperatures, gas flow compositions, reversibility, and so on; in all tested conditions, they outperform a homologous bare sucrose-derived carbon. Enhancing micropore volume allows achieving maximum adsorption capacity in pure CO2 (1.47 mmol g −1 at 30 °C/0.9 bar), whereas increasing surface N-content accounts for the highest selectivity in CO2 /N2 mixtures (20/80 v/v) at 35 °C/1 bar (maximum CO2 uptake 0.82 mmol g −1 ). The combination of a suitable C/N precursor and the hard templating synthetic route is effective for obtaining high-performing, sustainable, and reusable selective CO2 sorbents, without any activation steps or N-doping post-treatments. Graphical abstract: Image 1 Highlights: Nitrogen-containing ordered mesoporous carbons (NOMCs) are prepared by nanocasting. D-glucosamine is used as sustainable C/N source to obtain selective CO2 sorbents. Nanocasting allows fine-tuning of porosity and surface chemistry of NOMCs. CO2 uptake and CO2 /N2 selectivity are related to microporosity and N incorporation. High selectivity and reusability without post-synthesis activation or functionalization.